Reasons for attending and not attending a support group for recipients of implantable cardioverter defibrillators and their carers - Williams, Anne; Young, J.; Nikoletti, S.; McRae, S. (John Wiley and Sons, 2004)
There is evidence to suggest that people who have an implantable cardioverter defibrillator and their caregivers experience psychological distress. This qualitative descriptive study explored the experiences, concerns and needs of recipients of implantable cardioverter defibrillators and their caregivers who attended or did not attend a support group organized by a public hospital located in Perth, Western Australia, Australia. Eleven recipients of implantable cardioverter defibrillators and their caregivers participated in this study. Among those who attended the support group, four major themes were identified: providing information, connecting with others, helping others and attendance. Explanations for non-attendance included difficulties attending because of the location, not wanting to be reminded about the implantable cardioverter defibrillator, and a perception, among younger recipients, that the support group was comprised of mainly older recipients with whom they had little in common.